2011
DOI: 10.1002/ca.21215
|View full text |Cite
|
Sign up to set email alerts
|

Anatomist on the dissecting table? Dutch anatomical professionals' views on body donation

Abstract: Anatomical professionals know better than anyone else that donated bodies are a valuable asset to anatomical science and medical education. They highly value voluntary donations, since a dearth of bodies negatively affects their profession. With this in mind, we conducted a survey (n = 54) at the 171st scientific meeting of the Dutch Anatomical Society in 2009 to see to what extent anatomical professionals are willing to donate their own body. The results reveal that none of the survey participants are registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 14 publications
1
25
1
3
Order By: Relevance
“…Previous studies have suggested that being exposed to working with cadavers influences attitudes toward body donation (ŞEHIRLI, SAKA, SARIKAYA, 2004;CAHILL, ETTARH, 2008;PERRY, ETTARH, 2009;BOLT et al, 2012;ALEXANDER et al, 2014;PLAISANT et al, 2014). After their anatomy course, which included cadaver-based instruction, students were less keen to become donors or to advise their family to do so (CAHILL, ETTARH, 2008;PERRY, ETTARH, 2009;ALEXANDER et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that being exposed to working with cadavers influences attitudes toward body donation (ŞEHIRLI, SAKA, SARIKAYA, 2004;CAHILL, ETTARH, 2008;PERRY, ETTARH, 2009;BOLT et al, 2012;ALEXANDER et al, 2014;PLAISANT et al, 2014). After their anatomy course, which included cadaver-based instruction, students were less keen to become donors or to advise their family to do so (CAHILL, ETTARH, 2008;PERRY, ETTARH, 2009;ALEXANDER et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes toward cadavers, their role in education, and toward body donation among the general population, donors, and professionals (Sanner, 1994;Richardson and Hurwitz, 1995;Dluzen et al, 1996;Abu-Hijelh et al, 1997;Lagwinski et al, 1998;Arr aez-Aybar et al, 2004a;Boulware et al, 2004;S¸ehirli et al, 2004;Ajita and Singh, 2007;Bolt et al, 2010Bolt et al, , 2011Bolt et al, , 2012Chakraborty et al, 2010;McClea and Stringer, 2010;Wijbenga et al, 2010;Halou et al, 2013) seem to vary, following to a considerable extent the changes in the social and cultural landscapes of a country (e.g., Park et al, 2011;Cornwal et al, 2012). In the words of the British historian of medicine Roy Porter: "the body is pregnant with symbolic meanings, deep, intensely charged and often highly contradictory… Medical beliefs are always underpinned by cultural attitudes and values about the flesh" (Porter, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining sex differences in donation show inconsistent findings (e.g., Dluzen et al, 1996;Cornwall et al, 2012a). Other studies have found that those who were married (e.g., Dluzen, et al, 1996) or had a long-term partner (Bolt et al, 2010;Cornwall et al, 2012a) were more likely to register and that there was a greater willingness to donate among those who were more educated (Bolt, Venbrux, Eisinga, & Gerrits, 2012;Boulware et al, 2004;Cornwall et al, 2012a;Rokade & Gaikawad, 2012). Ethnicity among deceased donors was almost exclusively white Caucasian (e.g., Dluzen et al, 1996).…”
mentioning
confidence: 94%